On the Krull dimension of cofinite local cohomology modules
Let a be an ideal of a Noetherian ring R such that the category of a-cofinite modules is an Abelian subcategory of the category of R-modules. Let M be a finitely generated R-module such that the R-modules H^i_a (M) are a-cofinite for all integers iN_0. In this paper it is shown that H^i_a (M)≤ 1 for all integers i≥ 2. , number=1, journal=MATHEMATICA SCANDINAVICA, author=Bahmanpour, Kamal, year=2025, month=Mar.